The Use of VR-Box in the Counseling Process to Improve Mastery of Counseling Professional Lecture Materials for Guidance and Counseling Students - Gusman Lesmana; Zaharuddin Nur (Journal of Innovation in Educational and Cultural Research, 2025)
Adjustments to the transition period require each student to undergo reorientation from the online method to return to studying using the classical offline method. In response, there needs to be attention to finding new strategies for delivering classical counseling material. This research aims to determine the significance of the influence of cooperative learning on the development of students' public speaking skills. The population in this research was 150 students, and the sample was 40 students as research respondents. The research instrument is a questionnaire in the form of questions referring to indicators: knowing, understanding, applying, analyzing, synthesis, and evaluation. This research method is the Training of Trainers (TOT) method, which provides exposure to learning management training material (planning, organizing, implementing, and evaluating) and begins with testing through a quasi-experimental method as initial data. The research results show that the quality of lecture development using the Vr-Box learning strategy has a significant positive correlation trend. The results show a positive and significant influence of Vr-Box learning on the quality of guidance and counseling professional learning. The average increase in lecture quality score was 63.06, with a correlation coefficient between the Vr-Box learning strategy and student personality development of 0.426. From the results, it is recommended to focus learning more on the meaning of the process rather than the results. Learning evaluation must be equipped with process-based outputs and outcomes emphasizing the assessment of steps, activities, and student development during the learning process. The focus is not only on the final result (product) but also on how students achieve those results.